THE PRODUCTION OF FREEZE-DRIED PROBIOTIC FROM NAPPA CABBAGE JUICE BY LACTIC ACID BACTERIA - Ningrum, Dyah Ratna; Budiwati, Thelma Agustina; Nissa, Rossy Choerun; Mawarda, Panji Cahya (LIPI Press, 2018)
The suitability of nappa cabbage juice as raw material to produce freeze-dried probiotics by selected lactic acid bacteria, (Lactobacillus bulgaricus and Streptococcus thermophillus) has been investigated. The addition of filler in a form of rice and soybean flour mixture as protective material for viable cells was also assessed. The liquid mixture was fermented at 30oC for 24 h and sampled at 0 h, 14 h, 24 h and after it was freeze dried at -20oC. Soybean and rice flour mixture of 10% was added after 14 h of incubation. Titrable acidity, pH, and the number of viable cells were measured during fermentation and after the probiotics had been freeze dried. The carbohydrate, sucrose, lactose, and protein content of each freeze-dried probiotic was also determined. The freeze-dried probiotics analysis showed lactic acid bacteria reduced the pH to as low as 3.69 from 4.50 and increased the acidity from 2% to as high as 6.85%. The filler added to the mixture was found capable of partially protecting the viable cells to as high as 2.45 x 105 CFU/mL during freeze drying process. Lactobacillus bulgaricus exhibited slightly higher production of lactic acid than Streptococcus thermophilus even though Streptococcus thermophilus had higher viable cells. The nutrient composition of each freeze-dried probiotic showed closely similar content of carbohydrate and lactose whereas Streptococcus thermophilus had higher concentration of protein and sucrose. This study concludes that nappa cabbage juice could be utilized to produce freeze-dried probiotics.